Synthesis of Calcium Potassium Phosphate from Acetylene Gas Waste Using the Dissolution-Precipitation Method - Bernice Barbarossa Adine Romansa Patty; Reyka Dinar Aulia; Ketut Sumada; Lilik Suprianti (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
This study investigates the synthesis of calcium potassium phosphate (CaKPO?) composite using acetylene waste from acetylene gas production as a sustainable calcium source. The material was produced through a dissolution-precipitation process using phosphoric acid and potassium hydroxide, with variations in the mass of acetylene waste and precipitation pH. The results demonstrate that pH strongly influences yield, elemental composition, and crystal morphology, with the highest CaKPO? yield achieved at pH 5. SEM-EDX analyses reveal that low pH conditions favor calcium-rich, irregular crystal structures, while higher pH promotes potassium incorporation and the formation of more ordered crystalline domains. Overall, the study highlights the potential of acetylene waste valorisation for developing multinutrient fertiliser materials and supports the advancement of environmentally responsible resource use in line with the Sustainable Development Goals. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action